Australian lobbyist registers are not serving the purposes they were designed for - Robertson, N.; Kypri, K.; Stafford, J.; Daube, Mike; Avery, M.; Miller, P. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Australasian Professional Society on Alcohol and other Drugs. Introduction and Aims. There is widespread concern about the nature, extent and impacts of lobbying by industries selling unhealthy commodities, which threatens public health and undermines important democratic processes. In the last decade, all Australian jurisdictions (except the Northern Territory) have established lobbyist registers with the stated objective of increasing the capacity of government and the public to scrutinise lobbying. Our aim was to assess whether the registers are fulfilling this objective. Design and Methods. We conducted web searches of registers in Australian jurisdictions in 2014 and 2015 to determine what type of information they collected and whether data were accessible. We supplemented searches with e-mails and phone calls to registrars to clarify policies and seek additional information. Results. We found that the data were lacking in critical details and historical information was difficult or impossible to obtain. None of the registers required in-house lobbyists to register or to be bound by the Lobbying Codes of Conduct. None required that informal lobbying (e.g. by government relations staff within a company) be recorded, and none provided detailed information about the nature and extent of lobbying activities. Discussion and Conclusions. The registers do not meet the stated objective of making lobbying activity transparent to the Australian public. Timely access to comprehensive information is essential to help promote the rational development of policy concerning tobacco, alcohol and gambling problems. There is an urgent need to reform lobbyist registers to ensure that they are comprehensive and transparent.